Observations on the Growth Performance of Labeo dussumieri (Val.) in Mono and Mixed Culture Experiments - B., Madhusoodana Kurup (Fishery Technology, 2025)
Growth performance and production potential of an indigenous carp of Kerala, Labeo dussumieri (Val.) has been studied by culturing it alone and also in combination with Indian major carps. In monoculture trials, L. dussumieri attained a mean weight of 392 and 356 g at stocking densities of 3000 and 4000 ha’1, respectively within a period of 10 months. In composite culture trials when L. dussumieri (Thooli) was reared along with Catla, Rohu and Mrigal in the ratio 1:1:1:0.5, and the average weight attained by Catla, Rohu, Mrigal and Thooli within a period of ten months were 671, 602, 474 and 322 g, respectively at a stocking density of 6000 ha"1 whereas at a higher density of 8000 ha"1, the average weights registered were in the order of 557, 506, 397 and 283 g, respectively. These would work out to a gross production of 2698 and 3043 kg ha"1 at stocking densities of 6000 and 8000 ha"1, respectively. The growth attained by L. dussumieri was apparently poor in the experiments when ratio of the above four species was maintained at 1:1:1:1. Physicochemical and biotic parameters of the ponds were also studied.